Needs of social isolation, loneliness, and intergenerational interventions in the United States: a scoping review - Holloway, Jeremy; James, Dara L.; Robillard, Alyssa; Hermer, Janice; Hawley, Nanako; Sayeed, Owais (Frontiers in Public Health, 2024)
Social isolation and loneliness are major health concerns for older adults in the United States. This scoping review examines the effectiveness of intergenerational interventions aimed at reducing social isolation and loneliness among older adults in the United States, specifically through programs that engage university students from healthcare-related fields in one-on-one settings with older adults, as reports of lacking geriatric training of healthcare students causes elder neglect to persist in the healthcare workforce. The importance of addressing these issues is underscored by significant health risks and substantial economic burdens, with social isolation and loneliness potentially increasing mortality and costing Medicare an estimated 6.7 billion annually. Covering literature from 2010 to 2022, this review critically assesses the role of such interventions in fostering social connections and improving both physical and mental health outcomes. Despite the positive preliminary results indicating significant reductions in loneliness and enhancements in social networks among participants, the review highlights considerable gaps in current research, particularly in structured intervention curricula, demographic reporting and detailed intervention descriptions. This underscores the need for more rigorous and standardized research methodologies to better understand the effectiveness and potential of intergenerational programs as interventions against the detrimental effects of social isolation and loneliness among older adults.